Association of impaired cognitive function with balance confidence, static balance, dynamic balance, functional mobility, and risk of falls in older adults with depression - Zainab Khan; Ashi Saif; Neera Chaudhry; Adila Parveen (Aging Medicine, 2023)
Abstract Objectives Increased depression severity has been linked to cognitive impairment (CI). Importantly, CI is a known risk factor for impaired balance and falls. Therefore, this study aims to explore the relationship between CI and neuromuscular functions and secondarily it aims to find out if CI is a potential predictor for neuromuscular functions deficits in depressed elderly. Methods Eighty‐four depressed elderly participated in the study. Assessment for CI symptoms were done using Mini Mental Status Examination (MMSE) in subjects having confirmed depression. Neuromuscular functions such as balance confidence, static and dynamic balance, functional mobility, and fall risk were subjectively assessed using Activities‐specific Balance Confidence (ABC) Scale, Berg Balance Scale (BBS), Timed Up and Go (TUG) Test, and Performance Oriented Mobility Assessment (POMA), respectively. Results Pearson's analysis revealed that there was moderate positive linear‐correlation between MMSE and BBS (R = 0.382, p = <0.001) and between MMSE and ABC (R = 0.229, p = 0.036*). Further, regression analysis (R2) revealed that MMSE significantly predicted the neuromuscular functions using BBS [F(1, 82) = 14.013, p < 0.001, with an R2 of 0.146] and ABC [F(1, 82) = 4.545, p= 0.036*, with an R2 of 0.053]. Conclusion Results of this study points to an impaired CI as a possible factor in development of neuromuscular function impairment in depressed elderly.